Urgensi Sistem Penjaminan Mutu Internal Terhadap Peningkatan Mutu Di Sekolah Tinggi Ilmu Kepolisian - NDOLUANAK, YOFRAN HENGKI; Husnorofik, Zidni; Riyadi, Riyadi; Ridwan, Ahmad (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2023)
Abstract The Indonesia National Police must carry out reforms in an effort to provide excellent service to the community, including with a more humane, responsible and fair and transparent approach. One way to reform the police is that it must start from the education system in the police, namely when high-ranking officer candidates undertake education at the Police Science College (STIK). This condition underlines the importance of implementing an internal quality assurance system at the Police Science College (STIK). The implementation of an internal quality assurance system is used as the basis for controlling the quality management of higher education with national standards. There are several important exigencies obtained by the Police Science College (STIK) in the evaluation carried out by the internal quality assurance system which includes: (1) SPMI plays a role as a guarantee of educational quality standards, (2) SPMI plays a role as a guarantee of research quality standards and (3) SPMI acts as a guarantee of quality standards for community service. Keywords: Internal quality assurance system, Urgency, Police Science College